Facilitating Electroactive Site Density Determination during Fuel‐Cell Testing - Rifael Z. Snitkoff‐Sol; Lior Elbaz (ChemElectroChem)
The increase in performance and durability the platinum group metal (PGM)‐free catalysts makes them a viable alternative to PGM catalysts at the cathodes of low‐temperature fuel cells. The fuel‐cell performance strongly depends on the number of electroactive sites. Recently, a methodology for its quantification during fuel cell testing was presented based on applying low‐frequency Fourier‐transformed ac voltammetry (FTacV) and electrochemical impedance spectroscopy measurements. Herein, a physics‐based model that describes the potential drop in the catalyst layer is developed and the effects of the cell parameters on the higher harmonic components generated in FTacV measurements are numerically investigated. Herein, the model used in the previous work is validated and quantitative boundaries for its application to extract the number of electroactive sites in a fuel cell, enabling more precise analysis of this important and highly relevant quantity, are given.